1991
DOI: 10.1172/jci115113
|View full text |Cite
|
Sign up to set email alerts
|

Arginine vasopressin stimulates human mesangial cell production of endothelin.

Abstract: Endothelin (ET) is a vasoactive peptide produced by both endothelial and epithelial cells with documented mitogenic action on mesangial cells. The present studies were designed to test the hypothesis that ET is also produced by human mesangial cells (HMC)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

1992
1992
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(17 citation statements)
references
References 27 publications
0
16
0
1
Order By: Relevance
“…These changes in ECE activity were the consequence of a decrease in ECE-1 protein content, probably as a result of a decreased expression of its mRNA. demonstrated ET-1 synthesis by HMC [31][32][33][34], in our experimental conditions, HMC synthesized minimal amounts of ET-1. In fact, no immunoreactive ET-1 was detected in the supernatants of HMC alone and only a minimal expression of prepro-ET-1 mRNA appeared in these cells, independently of the presence or absence of HuVEC.…”
Section: Discussionmentioning
confidence: 93%
“…These changes in ECE activity were the consequence of a decrease in ECE-1 protein content, probably as a result of a decreased expression of its mRNA. demonstrated ET-1 synthesis by HMC [31][32][33][34], in our experimental conditions, HMC synthesized minimal amounts of ET-1. In fact, no immunoreactive ET-1 was detected in the supernatants of HMC alone and only a minimal expression of prepro-ET-1 mRNA appeared in these cells, independently of the presence or absence of HuVEC.…”
Section: Discussionmentioning
confidence: 93%
“…They suggested that ET-1 production by IMCD cells serves an autocrine function. Furthermore, other experiments have shown that angiotensin II [8] and arginine vasopressin (AVP) [8,9] are able to increase ET-1 release. Thus, it is possible that raised angiotensin II levels in CHF lead to increased production of ET-1 by the collecting ducts.…”
Section: Oooooooooooooooooooooomentioning
confidence: 99%
“…The binding data were comparable in their sensitivity for ET levels. However, the DCC assay is advantageous since it neither requires the secondary antibody conjugates nor the additional incubation time (16)(17)(18)(19)(20)(21)(22)(23)(24) h) and the subsequent washing of the precipitated material and centrifugation. The DCC assay is sensitive (1 pmol/ml), reproducible (<6% variation) and the intra-assay and inter-assay variations are less than 10%.…”
Section: Cross-reactivity Of the Antibodies With Big Endothelin (B-et)mentioning
confidence: 99%
“…Although initially demonstrated in porcine aortic endothelial cells, it is now known that several other cell types synthesize and release endothelin (5, 6,15,16), suggesting that endothelin may participate in autocrine and paracrine modulation of cell growth and function in many tissues. The role of ETs in regulation of cell function remains the subject of active investigation.…”
mentioning
confidence: 99%